ಕೊಂಕಣಿ ರಂಗಭೂಮಿ - Vasudeva Shanbhag (Karnataka Konkani Sahitya Academy, 2004)
This book briefs us about Konkani Theatre and other folk forms
Konkanni Rangabhoomi
Keywords: Konkani; ಕೊಂಕಣಿ ರಂಗಭೂಮಿ; Konkanni Rangabhoomi; Folk Culture; Konkani; Konkani